Association of caesarean scar defect with risk of abnormal uterine bleeding: results from meta-analysis - Xiao-Jing Xu; Jing-Xing Jia; Zi-Qiong Sang; Li Li (BMC, 2024)
Abstract Objective To investigate the association between caesarean scar defects and abnormal uterine bleeding through systematic literature review. Methods PubMed, Web of Science, Cochrane Library and Embase databases were searched based on PRISMA 2020 to include studies exploring abnormal uterine bleeding in women with caesarean scar defects. The combined relative risk (RR) of uterine bleeding, combined prevalence of abnormal uterine bleeding and combined RR of intermenstrual uterine bleeding were calculated using a fixed- or random-effects model. Results Ten studies involving 1,183 women with caesarean scar defects met the inclusion criteria for this study. Compared with women without caesarean scar defects, those with caesarean scar defects had a higher risk of abnormal uterine bleeding (RR: 3.22, 95% CI: 1.83-5.66) and intermenstrual bleeding (RR: 2.93, 95% CI: 1.91-4.50). The prevalence of abnormal uterine bleeding was approximately 0.46 (95% CI: 0.27-0.64), and across populations, women with a previous caesarean section who had undergone imaging specifically for gynaecological disease had a significantly higher prevalence of abnormal uterine bleeding (0.77, 95% CI: 0.65-0.89) than those with at least one caesarean Sect. (0.25, 95% CI: 0.10-0.39). Conclusion A significant association was observed between caesarean scar defects and abnormal uterine bleeding, with the former being a risk factor for the latter. However, previous studies have differed in the definition of caesarean scar defects and abnormal uterine bleeding, and more high-quality studies are needed to further investigate the relevant definitions and study results in the future.